Schisandrin B inhibits α-melanocyte-stimulating hormone-induced melanogenesis in B16F10 cells via downregulation of MAPK and CREB signaling pathways - Zhao, Na; Su, Xiaoming; Li, He; Li, Zhengyi; Wang, Yueyang; Chen, Jianguang; Zhuang, Wenyue (Bioscience, biotechnology, and biochemistry, 2021)
ABSTRACT Schisandrin B (Sch B), a lignan compound in Schisandra, possesses antioxidant, anti-inflammatory, and antiobesity activities. The effect of Sch B on melanogenesis and molecular mechanisms are still unknown. Therefore, we aimed to investigate the antimelanogenic effects of Sch B on α-melanocyte-stimulating hormone–induced B16F10 cells and elucidate the underlying molecular mechanisms. We found that Sch B significantly suppressed melanin content and mushroom tyrosinase (TYR) activity. Sch B treatment decreased the expression of TYR, melanocyte-inducing transcription factor (MITF), tyrosinase-related protein (TRP) 1, and TRP2. Moreover, Sch B modulated the phosphorylation of p38, extracellular-regulated protein kinase, c-Jun N-terminal kinase, and cAMP-response element binding protein (CREB), implying that these pathways may be involved in suppressing melanogenesis. Furthermore, we found that Sch B decreased melanogenesis by downregulating MITF and melanogenic enzymes via MAPK and CREB pathways. Overall, these findings indicate that Sch B has the potential use in whitening. Graphical Abstract Graphical Abstract The proposed mechanism of Sch B for inhibition of α-MSH-induced melanogenesis. Red arrows indicate Sch B activity, and black arrows indicate the direction of regulation.